Beyond the formalist-realist divide : the role of politics in judging - Tamanaha, Brian Z. (Princeton University Press, 2010)
According to conventional wisdom in American legal culture, the 1870s to 1920s was the age of legal formalism, when judges believed that the law was autonomous and logically ordered, and that they mechanically deduced right answers in cases. In the 1920s and 1930s, the story continues, the legal realists discredited this view by demonstrating that the law is marked by gaps and contradictions, arguing that judges construct legal justifications to support desired outcomes. This often-repeated historical account is virtually taken for granted today, and continues to shape understandings about jud.